Supporting Rights Clearance for Digitisation Projects with the ARROW Service - Freire, Nuno; Scipione, Gabriella; Muhr, Markus; Juffinger, Andreas (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2013)
The process of clearing the rights situation of a work for digitisation is very difficult to be performed for works that have been published during the 20th and 21st centuries. Although libraries hold materials of public interest, which should be made digitally available to a broader public, legal issues make it necessary to determine their exact copyright status before a library can digitise it. One of the major challenges in rights clearance is the significant fragmentation of rights information across multiple data sources, some of which are not remotely accessible. This makes the rights clearance process very demanding and expensive for libraries. Large-scale digitisation projects can digitise thousands of books per week, and therefore there is a significant need to develop faster ways to clear the copyright status of the books. In the ARROW and ARROW Plus projects (Accessible Registries of Rights Information and Orphan Works), a single framework is being established to combine and access rights information. It proposes to create a seamless service across a distributed network of national databases containing information that will assist in determining the rights status of works. Its goal is to support mass digitisation projects by finding automated ways to clear the rights of the books to be digitised. This paper describes the ARROW service from the perspective of libraries undertaking digitisation projects. It presents the complete ARROW workflow, how national bibliographies are used in ARROW, and the services that ARROW offers particularly for libraries.